Proses Penegakan Disiplin dan Penyelesaian Sengketa di Lingkungan Militer (Tindak Disiplin dalam Kegiatan Militer) - N, Naomi; Pasha, Anindya; Ismail, Umar Jafar; Haura, Tsaniyah Aqila; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2024)
According to Law Number 34 of 2004, Indonesia's defense sector is responsible for safeguarding the country's sovereignty, territorial integrity, safety, and dignity. The Indonesian military, known as Tentara Nasional Indonesia (TNI), performs this job. Military disciplinary actions are used in the military environment, however they can lead to conflicts if they do not correspond with established military values. This research, titled "The Application of Disciplinary Actions in the Military Environment" (Study of Decision Number: 78-K/PM.III-19/AD/III/2020), investigates the enforcement of law against TNI personnel implicated in situations of abuse by superiors against subordinates, for instance the Hendra case. The purpose of the research is to understand the application of disciplinary actions in military law, the process of dispute resolution, and the enforcement of discipline in the military environment, as well as the considerations of military judges in making their decisions